Rational Creatures and Matter in Eschatology According to Origen's On First Principles (Brill / Ferdinand Schöning, 2021)
The present article aims to study the relationship between rational creatures and matter in eschatology, according to Origen’s On First Principles. Firstly, the article reviews two preliminary issues, 1) the correspondence between beginning and end in Origen’s theology, and 2) the meaning of the expression “pre-existence of the soul” in modern scholarship. Secondly, the paper examines 3) the question regarding the initial relationship between mind and matter, namely, whether rational creatures had bodies from the beginning of their existence, and 4) the same problematic relationship in eschatology, namely, whether the bodies, after the resurrection, would be destroyed or transformed when the rational creatures reached the last stage of contemplation. Finally, 5) the article suggests that although Origen considered the final status of resurrected bodies to be an open question, he supported the hypothesis of the final transformation of matter, not its dissolution.